2011
DOI: 10.1089/vbz.2009.0028
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for West Nile Virus in Wild Birds from Northern Europe

Abstract: A total of 1935 migratory birds from 104 different species were captured in southeastern Sweden in 2005-2006 and tested for antibodies against West Nile virus (WNV). Overall, 46 birds (2.4%; binomial confidence limits, 1.8-3.2) were positive by blocking-ELISA, but only 2 (0.10%; binomial confidence limits, 0.0-0.4) had antibodies detectable by both blocking-ELISA and WNV neutralization test. ELISA-positive birds included long- and short-distance migrants likely exposed to WNV while wintering in or migrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
1
27
1
Order By: Relevance
“…The only WNV screening study of birds from the Nordic countries showed very low seroprevalence (0.1%) among the 104 sampled species, and no signs of exposure to WNV in the seven tested waterfowl species. [47] However, there are several reasons to include WNV in the present review. Firstly, WNV antibodies have been found in mute swans in Poland, Germany and Serbia.…”
Section: West Nile Virusmentioning
confidence: 99%
“…The only WNV screening study of birds from the Nordic countries showed very low seroprevalence (0.1%) among the 104 sampled species, and no signs of exposure to WNV in the seven tested waterfowl species. [47] However, there are several reasons to include WNV in the present review. Firstly, WNV antibodies have been found in mute swans in Poland, Germany and Serbia.…”
Section: West Nile Virusmentioning
confidence: 99%
“…However, sedentary bird species in Europe may also be exposed to a wide diversity of flaviviruses [16,67,78]. Parallel titration for antibodies against several flaviviruses using VNTs is therefore essential in identifying exposure to potentially emerging flaviviruses and is even more crucial in assessing the continued transmission of introduced flaviviruses in Europe [68,76,85,132,162,163,164]. Similar constraints exist in serosurveys of wild ungulates because the diversity of the flaviviruses that may circulate in these species is poorly known [165].…”
Section: Serological Cross-reactions Between West Nile and Relatedmentioning
confidence: 99%
“…Mosquito species from other genera are also susceptible to infection. There is now indirect evidence that WNV is transported by migratory birds to the temperate areas of Europe during spring migration [26-28]. Mammals are less important than birds in maintaining transmission cycles of the virus as viremia is too low in most of the mammal species to reinfect mosquitoes.…”
Section: Epidemiologymentioning
confidence: 99%